Double Chaining Algorithm: A secure symmetric-key encryption algorithm - Kurniawan, Daniar Heri; Munir, Rinaldi (2016 International Conference On Advanced Informatics: Concepts, Theory And Application (ICAICTA), 2016)
Technology is a key of innovation in any aspect of this modern era. In every technology, data becomes the most important asset to be protected. Many encryption algorithms are widely available and used in information security. Encryption can provide secure information across platform. Encryption algorithms are classified into two groups: symmetric-key (also called secret-key) and asymmetric-key (also called public-key). Generally, asymmetric-key encryption is used along side symmetric-key encryption to get the best performance of data transfer. Earlier many researchers have proposed various encryption algorithms such as AES, DES, Blowfish, etc. However, as security level is increasing, the time and complexity of algorithm is also increasing. This is the major cause of decreasing the speed and efficiency of the encryption system. In this paper we have proposed a new encryption algorithm "Double Chaining Algorithm (DCA)" which enhances the security performance. The DCA is a symmetric-key encryption algorithm that uses 128-256 bits key size. This algorithm uses XOR operation for the chaining process so that it has small complexity and can be implemented easily in hardware mode to increase its encryption process. This paper is an attempt to invent a new encryption model which is secure and very fast. The average Avalanche Effect in this algorithm is 0.996 out of 1.00. Moreover, the experiment and analysis result gives further proof of the DCA's strength.